Market timing and selectivity: an empirical investigation of european mutual fund performance - Salen, Tomás Coutinho Grosso de Oliveira (2017)
Mutual fund managers can enhance their returns by selecting assets with superior returns or by advantageously timing their portfolio allocation strategy to the stock market, or both. In the present study we examine the timing ability of mutual fund managers to denote the practice of these strategies as a way to achieve superior performance. Of the 193 European equity funds that followed active management strategies between January 2000 and December 2012, the results do not evidence that fund managers have denoted abilities to positively anticipate market movements (market timing). Nevertheless, the selectivity component of returns presents slightly positive results, despite the generally poor overall performance